Pulmonary rehabilitation for acute exacerbations of chronic obstructive pulmonary disease (COPD): A systematic review - Moore,E; Palmer,T; Newson,R; Quint,JK; Soljak,M (European Respiratory Society, 2016)
Background: Acute exacerbations of COPD (AECOPD) have a significant impact on healthcare utilisation, including physician visits and hospitalisations. The effect of pulmonary rehabilitation (PR) on hospitalisations for AECOPD is inconclusive.Methods: Medical databases were searched to assess the impact of PR on emergency hospitalisations for AECOPD. Cohort studies and randomised controlled trials (RCTs) reporting hospitalisations for AECOPD as an outcome were included. Meta-analyses compared exacerbation rates between eligible PR recipients and non-recipients before and after PR.Results: 18 studies were included in the meta-analysis. Admission rates per person-year were lower in the year following completion of PR. Results from 10 RCTs showed that the control groups had a higher overall rate of exacerbations than the PR groups (0.967, 95% confidence intervals (CIs) 0.669, 1.399 for control versus 0.615 95% CI 0.328, 1.155 for PR). Five studies compared admission numbers in the 12 months before and after PR, finding a significantly higher admission rate before (1.243, 95% CIs 0.661, 2.336) compared to after PR (0.472, 95% CIs 0.280, 0.794). The pooled result of three cohort studies found the reference group had a lower admission rate compared to the PR group (0.184, 95% CI 0.106, 0.317 for reference versus 0.282 95% CI 0.246, 0.323 for PR).Conclusions: Although results from RCTs suggested that PR reduces subsequent exacerbations, pooled results from the cohort studies did not favour PR, likely reflecting the heterogeneous nature of individuals included in observational research and the varying standards of PR programmes.